Media Advertisement Requirements: Disciplining Female Body for Job Hunting Vs. Islamic Philosophy of Disciplining Female Body - Qaddos, Maira; Sarwar, Dr. Muhammad Shabbir; Khan, Maham Zahid (Journal of Peace, Development and Communication, 2021)
In almost every ad for job for female candidates, it is mentioned that required females are expected to have pleasing personality, good communication skills and well-groomed appearance which is quite contradictory with Islamic philosophy of disciplining female bodies as Islam discourages objectification of women. This paper is an attempt to explore the gendered discourses prevailing in various organizations to discipline female bodies into docile ones for sexual appeal in the organizations. The study is qualitative in nature. For data collection mixed method of interviews (n=100) and thematic analysis of job advertisement (n=100) is done. Foucault’s perspective of disciplining is used as theoretical framework for the study as it will help in drawing the difference between requirements for disciplining female bodies for job hunting vs. Islamic philosophy of disciplining female bodies in a Muslim country like Pakistan. Analysis of the data gathered by thematic analysis of advertisements and 100 interviews was conducted by coding the data into various themes. The study concludes that certain disciplinary techniques like no veil, heavy make over, trendy dresses, high heels are expected from females to be selected for the job which are contradictory with Islamic philosophy. Islam doesn’t restrict females from working but it wants them to be in proper fully covered dresses so that they may be respected. However, these organizations want to use females only as sex symbols. This practice should be condemned to provide women with an opportunity to make better use of their capabilities.